2018
DOI: 10.1111/jocd.12777
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal aggravation of acne in summers and the effect of temperature and humidity in a study in a tropical setting

Abstract: Summary Background Effect of seasonality on acne and acne flare has varied interpretations depending on the geographical area of study. In tropical areas, factors like high temperature and humidity may cause acne flares. Aims To assess the seasonal variation of acne in patients and to correlate it with the monthly temperature and humidity over a period of 1 year. Methods A cross‐sectional study of acne patients was conducted for one year. The patient's acne was graded. Patients were specifically questioned abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 12 publications
7
47
0
1
Order By: Relevance
“…An Indian study found 82 (47.95%) out of 171 acne patients reported seasonal variations in the severity level of acne. It was statistically significant that there were more aggravated acne issues for acne patients in summer (average temperature 32.2°C, average humidity 49.8%) as compared to rainy (average temperature 31.0°C, average humidity 68.5%) and winter season (average temperature 15.1°C, average humidity 79.7%) ( 81 ). The study showed that hot weather was risk factors for acne.…”
Section: Resultsmentioning
confidence: 99%
“…An Indian study found 82 (47.95%) out of 171 acne patients reported seasonal variations in the severity level of acne. It was statistically significant that there were more aggravated acne issues for acne patients in summer (average temperature 32.2°C, average humidity 49.8%) as compared to rainy (average temperature 31.0°C, average humidity 68.5%) and winter season (average temperature 15.1°C, average humidity 79.7%) ( 81 ). The study showed that hot weather was risk factors for acne.…”
Section: Resultsmentioning
confidence: 99%
“…Here it must be noted that it is the vehicle that is the culprit and this is compounded by the enhanced comedogenicity with concomitant UV radiation[ 15 26 ] which is one of the possible causes of the reported summer flare in acne. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…It is known that high temperature can affect the rate of sebum secretion. It is also postulated that increased humidity might increase the amount of squalene in the skin [26]. In addition, studies have discovered that increased humidity and excess sweating lead to swelling of the epidermal keratinocytes [27].…”
Section: Acne and Maskmentioning
confidence: 99%
“…In addition, studies have discovered that increased humidity and excess sweating lead to swelling of the epidermal keratinocytes [27]. All these alterations lead to acute obstruction and acne aggravation [26] (Figure 1).…”
Section: Acne and Maskmentioning
confidence: 99%